Differential View on the Bile Acid Stress Response of Clostridioides difficile - Sievers, Susanne; Metzendorf, Nicole G.; Dittmann, Silvia; Troitzsch, Daniel; Gast, Viola; Tröger, Sophie Marlen; Wolff, Christian; Zühlke, Daniela; Hirschfeld, Claudia; Schlüter, Rabea; Riedel, Katharina (Frontiers in Microbiology, 2019)
Clostridioides difficile is an intestinal human pathogen that uses the opportunity of a depleted microbiota to cause an infection. It is known, that the composition of the intestinal bile acid cocktail has a great impact on the susceptibility towards a C. difficile infection. However, the specific response of growing C. difficile cells to diverse bile acids on the molecular level has not been described yet. In this study, we recorded proteome signatures of shock and long-term (LT) stress with the four main bile acids cholic acid (CA), chenodeoxycholic acid (CDCA), deoxycholic acid (DCA) and lithocholic acid (LCA). A general overlapping response to all tested bile acids could be determined particularly in shock experiments which appears plausible in the light of their common steroid structure. However, during LT stress several proteins showed an altered abundance in the presence of only a single or a few of the bile acids indicating the existence of specific adaptation mechanisms. Our results point at a differential induction of the groEL and dnaKJgrpE chaperone systems, both belonging to the class I heat shock genes. Additionally, central metabolic pathways involving butyrate fermentation and the reductive Stickland fermentation of leucine were effected, although CA caused a proteome signature different from the other three bile acids. Furthermore, quantitative proteomics revealed a loss of flagellar proteins in LT stress with LCA. The absence of flagella could be substantiated by electron microscopy which also indicated less flagellated cells in the presence of DCA and CDCA and no influence on flagella formation by CA. Our data break down the bile acid stress response of C. difficile into a general and a specific adaptation. The latter cannot simply be divided into a response to primary and secondary bile acids, but rather reflects a complex and variable adaptation process enabling C. difficile to survive and to cause an infection in the intestinal tract.